2022
DOI: 10.3390/su14094997
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on Subjects’ Seasonal Perception and Adaptive Actions in Naturally Ventilated Hostel Dormitories in the Composite Climate Zone of India

Abstract: A seasonal adaptive thermal comfort study was done on university students in naturally ventilated dormitories in the composite climate zone of India. A total of 1462 responses were collected from the students during the field study spread over the autumn, winter, spring, and summer seasons of the academic year for 2018 and 2019. A “Right Here Right Now” type of surveying method was adopted, and the indoor thermal parameters were recorded simultaneously using high-grade instruments. The subjects’ mean thermal s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 37 publications
(87 reference statements)
0
0
0
1
Order By: Relevance
“…Most studies of behavioral adjustments in India seem to link heat-coping strategies directly to the heat [49,50,52,90,91]. In this study, however, we found that the primary predictors of coping strategies tended to not to be HI measured during the 24-h study period, nor heat-related symptoms, nor even reports of discomfort in the heat.…”
Section: Discussioncontrasting
confidence: 79%
See 1 more Smart Citation
“…Most studies of behavioral adjustments in India seem to link heat-coping strategies directly to the heat [49,50,52,90,91]. In this study, however, we found that the primary predictors of coping strategies tended to not to be HI measured during the 24-h study period, nor heat-related symptoms, nor even reports of discomfort in the heat.…”
Section: Discussioncontrasting
confidence: 79%
“…Adaptive thermal comfort studies in India have tended to focus on the potential benefits of a narrow range of heat-coping behaviors-primarily opening doors/windows, clothing adjustments and the use of fans [47,49,50,56,90,91]. While participants in this study also used these strategies, they were far from universally practiced, and often ineffective.…”
Section: Discussionmentioning
confidence: 97%
“…Parameter-parameter keselesaan terma yang disebutkan di atas menjadi sebahagian daripada kajian apabila prinsip keselesaan terma mudah suai diterapkan untuk mencatat respons terma subjek dalam kajian lapangan [33]. Keselesaan terma mudah suai melalui pelbagai kajian lapangan telah menunjukkan potensi besar dalam penilaian persekitaran terma dalaman dan mengurangkan penggunaan tenaga bangunan tanpa menafikan keselesaan penghuni [8].…”
Section: Pendahuluanunclassified
“…Indoor natural ventilation and air quality [1,15,16] Outdoor wind and pollutant diffusion [17][18][19][20] Pedestrian wind [21][22][23][24][25] Ventilation and energy saving [26] Wind energy utilization [27,28] Campus thermal comfort Indoor ventilation and thermal comfort [29][30][31][32] Outdoor wind and thermal comfort [33][34][35] Campus microclimate, mainly involving the wind environment Based on regional climate characteristics and layout form [36,37] Microclimate evaluation [38] Campus wind environment and health Health-related performance [39,40] Influencing factors of natural ventilation on campus Influence of natural ventilation on the façade of the building [41] Influence of atrium on natural ventilation [42] Influence of courtyard on natural ventilation [43] Influence of campus building layout on ventilation [44] Influence of human behavior mode on ventilation [45][46][47] Campus wind simulation method CFD numerical simulations based on different software [48][49][50] Simulation comparison of two turbulence models (RAN and LES) [51] Wind tunnel experiment [52] Fluent, Phoenics, OpenFOAM, and other commonly used CFD simulation software are among those found in the literature on wind environment simulations of campus buildings....…”
Section: Campus Natural Ventilationmentioning
confidence: 99%